Life satisfaction is the most significant determinant of quality of life in the elderly (Universa Medicina, 2021)
BackgroundQuality of life tends to decrease as age increases. This study aimed to determine the most significant risk factors (family support, spirituality, and life satisfaction) for the elderly’s quality of life. MethodsThis was a cross-sectional study of 101 subjects aged ³60 years in West Jakarta. The variables were assessed using the World Health Organization Quality of Life–BREF (WHOQOL–BREF), Family Support, Daily Spiritual Experience Scale (DSES), and the Satisfaction with Life Scale (SWLS) instruments. Multivariate logistic regression was used to analyze the association between quality of life and its determinant factors.ResultsBased on sociodemographic characteristics, the respondents were mostly women (66.3%), had more than nine years of education (79.2%), and were married (56.4%). The analysis showed that life satisfaction was significantly associated with overall quality of life (OR=9.71; 95% CI:2.04–46.26; p=0.004) and general health (OR=7.52; 95% CI:1.70–33.25; p=0.008). Life satisfaction was also a risk factor for the environmental domain (OR=36.02; 95% CI:5.07–255.82; p